Customer service : Skills for Success - Lucas, Robert W. (2022)
This title features how-to topics for the customer service student. It covers the concepts and skills needed for success in business careers, including listening techniques, verbal and nonverbal communication and use of technology. This edition addresses many market changes such as the impact of the COVID-19 pandemic, working in remote teams, and greater focus on customers with disabilities.
Includes bibliographical references and index.
Keywords: Customer services; Business and Management